Educação ambiental e o descarte correto de resíduos sólidos: orientações didáticas para os professores do 4º e 5º ano do Ensino Fundamental da U.E.B. Olinda Desterro - SILVA, Letícia Mendonça da (2021)
This dissertation has the aim to investigate how environmental education and the correct disposal of solid waste in the 4th and 5th year of Elementary School of the Basic Education Unit of Olinda Desterro – municipal school in São Luís/MA have been worked on, from the perspective of teachers, with the purpose to producing a brochure of didactic guidelines with methodological teaching proposals that consider the social context of the students. This is a research classified as applied, regarding its nature, exploratory and descriptive, in terms of objectives, from the perspective of Prodanov and Freitas (2013) and Gil (2009), and also qualitative, in terms of the approach, in the perspective of Farias Filho and Arruda Filho (2013). Therefore, a theoretical study was carried out on the legal aspects of environmental education in Brazil, such as: the Federal Constitution of 1998, the National Curriculum Parameters of 1997, the National Policy on Environmental Education of 1999, the National Policy on Solid Waste 2010, the Curriculum Guidelines for Environmental Education 2012, the Maranhão State Environmental Education Plan of 2018, the Common National Curriculum Base of 2017 and Decree No. 48911 of March 14, 2017 that created the Ecopoints in the city of São Luís /MA, among others. It also addresses solid waste disposal in teaching practices. Subsequently, a survey of the studies (theses and dissertations) was carried out in the CAPES Theses and Dissertations Bank dealing with environmental education in the early years of the elementary school in the period ranging from 2015 to 2019. Then, the methodology and analysis of the collected data are described. Regarding the procedures, the research presents traces of a case study, according to Gil (2009), being performed in a municipal public school in São Luís/MA, the Olinda Desterro Basic Education Unit. As a data collection instrument, the online questionnaire was used with teachers from the 4th and 5th grades of elementary school. The collected data were studied through a statistical analysis, according to Gerhardt and Silveira (2009). It was found that the teachers did not have, in their initial and continued training, an in-depth study of environmental issues that could provide a theoretical methodological basis for the development of activities in the school context. In general, the teachers reported that the work with this theme occurs infrequently, and sporadically. Finally, from the data analysis, a booklet of didactic guidelines was elaborated, which constitutes material for studies and reflections with methodological proposals for the work with environmental education, with a focus on the correct disposal of solid waste. Lastly, it is believed that this work can bring contributions, both theoretical and practical, to the planning and working with environmental education and the correct solid waste disposal in the 4th and 5th grade of elementary school.